Mutagenesis of Highland barley (Hordeum vulgare L. Var. nudum) using nitrogen ion beam implantation: screening of phenotypic variations and comparative transcriptome analysis - Hao-Yue Yu; You-Huan Zhang; Hang Li; Hong Feng (BMC Genomics)
Abstract Background Highland barley (Hordeum vulgare L. var. nudum) is a key crop of the Qinghai-Tibet Plateau, renowned for its nutritional value and exceptional adaptability to high-altitude environments. Induced mutagenesis offers a powerful approach to developing new crop varieties and elucidating the genetic basis of functional traits. Results In this study, nitrogen ion beam implantation was employed to induce mutations in the highland barley cultivar Kunlun 14 (K14), generating 71 novel mutation materials and enriching the genetic resources for barley breeding. Phenotypic trait correlation analysis identified two mutation lines exhibiting significant variations: E8-38 with highly increased 1000-grain weight, and D7-67 displaying a two-row spike phenotype. Comparative transcriptomic analysis was applied to the above two mutation materials. It was revealed that the high 1000-grain weight of E8-38 was driven by synergistic regulation of phytohormone signaling, metabolic pathways, and epigenetic modifications, particularly the upregulation of the cytokinins signaling pathway and starch metabolism genes. In D7-67, the two-rowed spike phenotype was underpinned by the upregulation of VRS1 genes. Adaptive mechanisms to high-altitude environments were investigated, revealing upregulation of PAL and 4CL genes in phenylpropanoid biosynthesis, which enhances UV resistance and antioxidant capacity. Additionally, optimization of the photosynthetic pathway may contribute to acclimation under harsh stress conditions. Through PPI analysis, BZIP transcription factors were found to regulate downstream genes, facilitating adaptation to light changes and oxidative stress. Conclusion Nitrogen ion beam implantation was demonstrated to be an efficiency method to introduce mutation on the highland barley, generating a set of mutation materials with a wide range of genetic variations. Through comparative transcriptomic analysis, this study elucidates the molecular basis underlying the 1000-grain weight and spike-type mutants, as well as the adaptive mechanisms enabling highland barley to thrive in high-altitude environments. These findings provide critical insights into the genetic and molecular mechanisms driving high-yield and stress-resilient traits in highland barley.